Homogeneity of coral reef communities across 8 degrees of latitude in the Saudi Arabian Red Sea. Issue 2 (30th April 2016) - Roberts, May B.; Jones, Geoffrey P.; McCormick, Mark I.; Munday, Philip L.; Neale, Stephen; Thorrold, Simon; Robitzch, Vanessa S.N.; Berumen, Michael L.
Abstract: Coral reef communities between 26.8°N and 18.6°N latitude in the Saudi Arabian Red Sea were surveyed to provide baseline data and an assessment of fine-scale biogeography of communities in this region. Forty reefs along 1100 km of coastline were surveyed using depth-stratified visual transects of fish and benthic communities. Fish abundance and benthic cover data were analyzed using multivariate approaches to investigate whether coral reef communities differed with latitude. A total of 215 fish species and 90 benthic categories were recorded on the surveys. There were no significant differences among locations in fish abundance, species richness, or among several diversity indices. Despite known environmental gradients within the Red Sea, the communities remained surprisingly similar. The communities do, however, exhibit subtle changes across this span of reefs that likely reflect the constrained distributions of several species of reef fish and benthic fauna. Highlights: 215 fishes and 91 benthic categories were assessed at 40 Saudi Red Sea reefs. Offshore reef communities in the Red Sea across 1100 km have similar assemblages. A current eco-region boundary at 20°N latitude may need to be reconsidered. This is timely baseline data for a region expected to experience rapid changes.